2017
DOI: 10.1002/jhet.2835
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis, Antimicrobial Studies, and Docking Simulations of New Bis(4,5‐dihydropyrazole) Derivatives

Abstract: A novel series of bis(3-thienyl-4,5-dihydropyrazoles) has been synthesized by the cyclization reactions of bischalcones with phenyl hydrazine in basic medium. The O-alkylation reactions of chalcones with suitable 1,ω-dibromoalkanes in the presence of anhydrous K 2 CO 3 , dry acetone, and Bu 4 N + I À as PTC lead to the formation of bischalcones in good yields. The chalcone required was obtained from the Claisen-Schmidt condensation reaction of 2-acetylthiophene with 3-hydroxybenzaldehyde. Structures of prepare… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 27 publications
0
6
0
Order By: Relevance
“…The reaction mixture was cooled and provided an off white solid, which was filtered and dried. To obtain pure product, the resulting solid was crystallized using methanol as solvent 4a …”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The reaction mixture was cooled and provided an off white solid, which was filtered and dried. To obtain pure product, the resulting solid was crystallized using methanol as solvent 4a …”
Section: Methodsmentioning
confidence: 99%
“…To obtain pure product, the resulting solid was crystallized using methanol as solvent 4a. [36] 4a: off white solid; yield: 84%; m.p. : 112°C to 114°C; IR (KBr) υ max (cm…”
Section: Synthesis Of 5-(4-methoxyphenyl)-n1-diphenyl-45-dihydro-mentioning
confidence: 99%
“…With the best of our efforts, only three papers incorporating the study of bispyranopyrazoles could be found. [36][37][38] In continuation of an ongoing study on bisheterocycles, [39][40][41][42][43][44] the present research work was focused on the synthesis of new rigid chain linked bis(pyranopyrazoles) 3a-f using three component condensation reactions of malononitrile, pyrazolone and dibenzaldehydes. The major impetus behind these investigations was to study the antimicrobial and antioxidant properties of the newly prepared symmetrical bisheterocycles.…”
Section: Introductionmentioning
confidence: 99%
“…The developments of the new proficient antibacterial therapies are the significant alternatives treatments for the conventional drug resistance bacteria and fungi . So to control the various infectious diseases and increasing microbial resistance, synthetic chemists have been organizing their researches upon the designing and preparations of the broad spectrum antimicrobial .…”
Section: Introductionmentioning
confidence: 99%